2021
DOI: 10.1021/acsami.0c22006
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Driven and Creep-Enabled Interface Evolution in Sodium Metal Batteries

Abstract: All-solid-state batteries (ASSBs) using an alkali metal anode and a solid-state electrolyte (SE) face several problems due to poor physical and electrical contact. Recent experiments have shown that applying a stack pressure can improve the interface contact and suppress void formation. The mechanical properties of Na metal are different from those of Li metal, leading to differences in the mechanisms of the pressure-dependent interface evolution. Herein, we report a three-dimensional time-dependent model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…Note that the creep due to the pressure buildup in the cell causes the smoother surface of Na upon longer open-circuit potential storage. 39 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the creep due to the pressure buildup in the cell causes the smoother surface of Na upon longer open-circuit potential storage. 39 41 …”
Section: Resultsmentioning
confidence: 99%
“…Considering the fact that increased E a (SEI) over time was observed for both Li-glyme and Na-glyme systems, the observed morphology and thickness of SEIs imply the densification (or compaction) of the SEIs. Note that the creep due to the pressure buildup in the cell causes the smoother surface of Na upon longer open-circuit potential storage. …”
Section: Resultsmentioning
confidence: 99%
“…Kasemchainan et al [ 41 ] suggested that a stacking pressure of 5‐7 MPa can be favorable for Li metal stripping and plating during a steady electrochemical cycling. A 3D time‐dependent model ( Figure 9 a) for tracking the evolution of interfaces formed between Na metal and Na‐β"‐Al 2 O 3 was reported by Zhang et al [ 99 ] The differences due to contact elastoplasticity are larger than the differences in metal creep effects. The increased stack pressure can lead to lower creep due to a more conformal contact at the high pressure.…”
Section: Strategies For Sodium Metal Stabilizationmentioning
confidence: 99%
“…Reproduced with permission. [ 99 ] Copyright 2021, American Chemical Society. b) Schematic of the insights into Na + ion transfer at Na/NASICON interface improved by uniaxial compression.…”
Section: Strategies For Sodium Metal Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation